2016
DOI: 10.1111/clr.12908
|View full text |Cite
|
Sign up to set email alerts
|

Lateral approach for sinus floor elevation: large versus small bone window – a split‐mouth randomized clinical trial

Abstract: A reduction of window dimensions did not affect the safety of the surgical procedure. The two testing techniques showed no statistically significant differences in surgical intervention duration. Patients' opinion at 7-day and 14-day post-op showed a preference for test procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 19 publications
3
41
2
1
Order By: Relevance
“…Pain levels recorded in lSFE group are consistent with those reported at 7 and 14 days postsurgery in the randomized trial by Baldini et al. (), where similar dimensions of the antrostomy (8 × 10 mm) were adopted in one study arm, and those reported during the first week postsurgery in another randomized trial (Temmerman et al., ). Also, consistently with the study by Temmerman et al.…”
Section: Discussionsupporting
confidence: 86%
“…Pain levels recorded in lSFE group are consistent with those reported at 7 and 14 days postsurgery in the randomized trial by Baldini et al. (), where similar dimensions of the antrostomy (8 × 10 mm) were adopted in one study arm, and those reported during the first week postsurgery in another randomized trial (Temmerman et al., ). Also, consistently with the study by Temmerman et al.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the total gain in height after 9 months was 7.7 mm for group A and 9.4 mm for group B. This outcome is in agreement with the outcomes of another randomized clinical study (8.5‐8.7 mm), in which the antrostomy was prepared with two different dimensions …”
Section: Discussionmentioning
confidence: 99%
“…Indications concerning the window size vary from author to author [15–21]. Different authors suggest that the lower antrostomy line should be positioned either flush with the sinus floor or up to 2-3 mm above it [1, 12, 22–24].…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, no systematic investigation of the effect of the window design, size, and position on complication rates or effort required to carry out sinus lift surgeries has been carried out. Indications concerning the window size vary from author to author [ 15 – 21 ]. Different authors suggest that the lower antrostomy line should be positioned either flush with the sinus floor or up to 2-3 mm above it [ 1 , 12 , 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%